Pediatric Medicine Development: An Overview and Comparison of Regulatory Processes in the European Union and United States. (May 2017) - Penkov, Dobromir; Tomasi, Paolo; Eichler, Irmgard; Murphy, Dianne; Yao, Lynne P.; Temeck, Jean
Pediatric legislation in the US and the EU is driving pediatric product development on an international scale. To facilitate harmonization and global development of pediatric medicines, it is important to understand the legislative requirements that must be met along with incentives that exist in the US and the EU to include pediatric patients in therapeutic clinical trials. Although there are many similarities, differences exist. This review is an effort to enhance understanding of the pediatric legislation in both regions. It is intended as an overview to supplement the region-specific legislation and guidance documents that are available on the websites of the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Despite differences, the goal of the legislation in both the EU and the US is to incentivize and require timely, ethical, and sound scientific development of pharmaceutical products for the pediatric population and to provide information for their safe and effective use.